Research Activity in Un-Aided Engineering Colleges a Review, Need & Hurdles - Handa, C. C. (Journal of Engineering Education Transformations, 2011)
The Technological growth index will decide the progress of the country. There is a phenomenal growth in the infrastructure for providing science&technical education. The growth&development of technology is decided by extent of research activity undertaken not only at industries levels but also at institutional level. Research activities are conducted at institutional- graduate&postgraduate level- but lack in direction and goal. The research activities carried out at post-graduate level&doctorial level are not need oriented but executed to satisfy requirement for getting degree as a part of qualification enhancement. The research work done at postgraduate&doctorial level is many times not application oriented and is never used after completion of degree. Freedom and autonomy are keywords, in the promotion of research, especially in foreign universities, is encouraging the local talent with lucrative offers, causing brain drain? Scientific&technological achievements could be crucial for our survival as a self- reliant country. Author has made an attempt to emphasis the need&growth of research activity in comparison to the growth of technical education. An effort is made towards identifying the reasons for lack of cult, apathy fo r research and its application. Hurdles in growth of research activity at institutional level are identified. A sincere exercise is done to enlist the remedies and provide motivation for encouraging the core and applied research, at science&technical institute level. A SWOT Analysis approach is also suggested.